Análise da efetivação dos direitos fundamentais dos refugiados venezuelanos residentes no estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Nation-states with failed economies and authoritarian political regimes lead the populations of their territories to rethink new destinations for living. The struggle for refuge aims to rebuild violated human dignity and to be recognized as a subject of rights. During the process of displacement and adaptation, there are several difficulties faced by the migrant subject, which permeate the route, the way of migrating, and the difficulties within the receiving country. Understanding that Brazil is a country that has one of the most welcoming legislations for the person in a refugee situation, and the high number of Venezuelan migrants who seek the territory in the perspective of finding shelter, the present work analyzes the performance of the State of Amazonas in welcoming this population that sought the region between the period from 2017 to 2019, due to the simultaneous crises experienced in Venezuela, and the growing number of people who took refuge in the State during this period. As a problem question, we sought to answer: what public policies did the State of Amazonas adopt to remedy or alleviate the social inequalities that affected the Venezuelan population in a situation of vulnerability in the territory? As a general objective, the effectiveness of the fundamental rights of Venezuelan refugees who resided in the State in a situation of vulnerability between 2017 and 2019 was analyzed. Methodologically, the exploratory-descriptive method was used, given the need to use official data to analyze the conditions of refugees in the territory. International migrations were discussed, arriving at migration in Amazonas, the relevance of the socio-anthropological context of migratory processes was addressed, then the core of the discussion is brought, which corresponds to the Venezuelan exodus in Amazonas, ranging from the humanitarian crisis in Venezuela, to the action of the state entity to recognize this population the same rights that are recognized to nationals living in the region, in addition, the importance of legal norms that deserve attention by the State was raised, finally, the role of public policies in the realization of migrants' rights was discussed as a way to ensure the human dignity of this group that lives in a vulnerable situation.
Analysis of the realization of the fundamental rights of venezuelan refugees living in the state of Amazonas
Keywords: Refugiados venezuelanos - Direitos fundamentais; Refugiados venezuelanos - Amazonas; CIENCIAS SOCIAIS APLICADAS: DIREITO: DIREITO PUBLICO: DIREITO CONSTITUCIONAL; Migração; Refugiados venezuelanos; Dignidade humana; Amazonas; Igualdade de direitos